Associations between the workplace-effort in psychosocial risk management and the employee-rating of the psychosocial work environment – a multilevel study of 7565 employees in 1013 workplaces. Issue 5 (July 2017) - Thorsen, Sannie Vester; Madsen, Ida Elisabeth Huitfeldt; Flyvholm, Mari-Ann; Hasle, Peter
Aims: This study examined the association between the workplace-effort in psychosocial risk management and later employee-rating of the psychosocial work environment. Method: The study is based on data from two questionnaire surveys – one including 1013 workplaces and one including 7565 employees from these workplaces. The association was analyzed using multi-level linear regression. The association for five different trade-groups and for five different psychosocial work environment domains was examined. Results: Limited but statistically significant better employee-ratings of the psychosocial work environment in the respective domains were observed among Danish workplaces that prioritized "development possibilities for employees, " "recognition of employees, " "employees influence on own work tasks, " good "communication at the workplace, " and "help to prevent work overload." Conclusion: Danish workplaces with a high effort in psychosocial risk management in the preceding year had a small but significantly more positive rating of the psychosocial work environment by the employees. However, future studies are needed to establish the causality of the associations.